Psychological, Biological, and Behavioral Predictors of Changes in Eating Attitudes from Age 13 to 17 Y Among Urban, Black South African Adolescents (P18-102-19) - Kowalski, Alysse (Curr Dev Nutr, 2019)
OBJECTIVES: Psychological, biological, and behavioral predictors of change in adolescent eating attitudes have not previously been examined in a South African context. We aimed to characterize patterns and predictors of trends in eating attitudes from age 13 to 17 y in an urban South African cohort. METHODS: Data come from the Birth to Twenty Plus birth cohort in Soweto-Johannesburg. The 26-item Eating Attitudes Test (EAT-26) was administered at ages 13 and 17 y. Self-esteem, weight control behavior, and body mass index (BMI) were assessed at the same ages. Sex-specific associations of changes in predictors over time with changes in the EAT-26 were modeled using linear regression. RESULTS: At age 13 y, EAT-26 (mean ± SD) was 9.92 ± 7.34 with no difference between girls and boys. At age 17 y, EAT-26 was higher, reflecting poorer eating attitudes, among girls (11.14 ± 8.75) than boys (10.06 ± 6.77). From age 13 to 17 y, self-esteem scores improved slightly (0.36 ± 4.95), with no difference by sex, while BMI increased more among girls (2.57 ± 2.34 kg/m(2)) than boys (1.72 ± 2.21 kg/m(2)). More girls reported a weight loss attempt at age 17 (32%) than at 13 y (19%), while more boys reported trying to lose weight at age 13 (14%) than at 17 y (9%). Among girls, greater BMI increase from age 13 to age 17 y was associated with higher EAT-26 (β = 0.52 per kg/m(2), 95% confidence interval [CI]: 0.09, 0.95), and increased self-esteem score was associated with decreased EAT-26 (β = −0.40, CI: −0.59, −0.22). Similar associations were observed among boys. Compared to those whose weight control behavior did not change, attempted weight loss at age 13 y but not at age 17 y was associated with decreased EAT-26 (β = −3.67, CI: −7.3, −0.03) among girls, while among boys, attempted weight loss at age 17 y but not at age 13 y was associated with increased EAT-26 (β = 7.16, CI: 3.53, 10.8). CONCLUSIONS: In a longitudinal sample of Black South African adolescents, improved self-esteem and decreased BMI were each associated with improved eating attitudes in both boys and girls, while associations of patterns of weight control behavior with eating attitudes differed by sex. FUNDING SOURCES: NIH Fogarty International Center, Bill & Melinda Gates Foundation, Wellcome Trust, University of the Witwatersrand, South African Medical Research Council. SUPPORTING TABLES, IMAGES AND/OR GRAPHS: